2006
DOI: 10.1111/j.1741-1130.2006.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pervasive Developmental Disorders in Two Canadian Provinces

Abstract: Although it is generally accepted that the proportion of children diagnosed with pervasive developmental disorders (PDDs) has increased in the past two decades, there is no consensus on the prevalence of these conditions. The accompanying large rise in demand for services, together with uncertainty regarding the extent to which the observed increases are due to a true change in risk, has made PDDs a major public health concern. As few data exist on the prevalence of PDDs in Canada, the aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
1
25
0
2
Order By: Relevance
“…Recent work by Emam and Farrell (2009) and Ouellette-Kuntz, Coo, and Yu (2006) reflect challenges inherent in the identification and delivery of services to children with ASD in both the United Kingdom and Canada. More aggressive evaluation of policy implementation and its subsequent dissemination may provide policy makers, practitioners, and advocates alike some much-needed guidance on how and where to devote resources.…”
Section: Discussionmentioning
confidence: 98%
“…Recent work by Emam and Farrell (2009) and Ouellette-Kuntz, Coo, and Yu (2006) reflect challenges inherent in the identification and delivery of services to children with ASD in both the United Kingdom and Canada. More aggressive evaluation of policy implementation and its subsequent dissemination may provide policy makers, practitioners, and advocates alike some much-needed guidance on how and where to devote resources.…”
Section: Discussionmentioning
confidence: 98%
“…Some reports suggest humans may confront analogous risks. A high prevalence of ASD has been associated with coastal communities adjacent to marine environments with high levels of DA [84, 112-114]. Taken together, developmental exposures to domoic acid and other natural and synthetic ligands of glutamate receptors deserve attention for their potential contributions to ASD susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…ASDs are a serious and relatively common problem in society; the prevalence of autistic disorder was reported as being between 30 and 60 per 10,000 (Chakrabarti and Fombonne 2005;Chudley et al 1998;Ouellette-Kuntz et al 2006;Fombonne 2003). A comprehensive examination of prevalence of ASD across 14 sites in the United States revealed that 0.66% of children at 8 years of age were diagnosed with an ASD, (range = 3.3-10.6 per 1,000 children), with most sites reporting a rate between 5.2 and 7.6 per 1,000 children (Rice 2007).…”
Section: Introductionmentioning
confidence: 99%